Screening for intrauterine growth retardation using ratio of mid-arm circumference to occipitofrontal circumference. Issue 6527 (19th April 1986) - Meadows, N J; Till, J; Leaf, A; Hughes, E; Jani, B; Larcher, V
Abstract : Uncritical application of standard weight percentile charts, derived from white infants, to infants from different ethnic groups may result in an overestimate of the incidence of intrauterine growth retardation in those groups. The ratio of mid-arm circumference to occipitofrontal circumference was studied in 194 babies (49 Asian, 58 black, and 87 white). In contrast with birth weight the ratio did not vary among the ethnic groups; it was also independent of sex. In a prospective study of 64 neonates whose weight was below the 10th percentile on standard charts the ratio of mid-arm circumference to occipitofrontal circumference was a more accurate predictor than weight of those infants who would develop symptoms associated with intrauterine growth retardation. The ratio of mid-arm circumference to occipitofrontal circumference therefore provides a simple, accurate, and cheap way of assessing intrauterine growth retardation in areas with a large multiethnic population, where birth weight varies greatly.